Developing Visual Elements on the Web - Ricky W. Telg; Laura M. Gorham; Tracy Irani (EDIS)
Knowing how to create and design a website is a valuable skill.  This 3-page publication is on developing visual elements (colors, images, navigation, and links) on the web and is the fourth of the Writing and Designing for the Web series. This four-part series explains general tenants of good web design, covers the terminology and techniques involved in creating appealing, user-friendly websites, and also discusses basic HTML coding and developing visual elements for the web. Written by Ricky Telg, Laura Gorham, and Tracy Irani, and published by the UF Department of Agricultural Education and Communication, August 2015.